PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI INDOGROSIR CIBINONG - Osta Nababan, Benny; ., Ramadhan (Economicus, 2018)
This study aims to determine the effect of the marketing mix including products, prices, promotions, and locations, both simultaneously and partially on purchasing decisions at Indogrosir Cibinong. The results of data analysis show that the product, price and location have a significant effect on purchasing decisions while the promotion has no significant effect on purchasing decisions. The marketing mix consisting of products, prices, promotions and purchasing decisions jointly influences purchasing decisions. The coefficient of determination (R2) is 0.351 which means that 35.1% of purchasing decisions in Indogrosir Cibinong are influenced by product variables, price, promotion, and location, while the remaining 64.9% is influenced by other variables outside the research. Suggestions that can be given in this study are: (1) Indogrosir Cibinong should pay attention to product factors by paying attention to products that are not close to expiration, good quality products, attractive packaging, and not dusty and neat; (2) Price factor by providing affordable prices, prices according to product quality, prices listed in accordance with the price that must be paid, the price offered is competitive and relatively cheap, and prices are in accordance with the benefits of the product; (3) Location factors by paying attention to parking arrangements, parking areas of two or four-wheeled vehicles are quite adequate, the location of Indogrosir is easily accessible by public transportation, as well as the strategic location of Indogrosir.